Pengaruh Pupuk Daun dan Arang Aktif pada Media Subkultur II terhadap Pertumbuhan Bibit Anggrek Phalaenopsis - Ferziana Ferziana (Jurnal Penelitian Pertanian Terapan, 2013)
The purpose of this study is to obtain the best media as media subculture II in accelerating the growth of Phalaenopsis orchid seedlings with foliar fertilizers as well as the addition of activated charcoal. Research using completely randomized design with 10 treatments and 3 replication. Data were analyzed with analysis of variance and followed by LSD test at 5% level. Treatment reseach is: KH2A0: Kristalon green 2 g.l-1+ Without activated charcoal, KH2A1/2 : Kristalon green 2 g.l-1+ Activated charcoal ½ g.l-1,KH2A1: Kristalon green 2 g.l-1+ Activated charcoal g.l-1 , KH 2A11/2 : Kristalon green 2 g.l-1 + Activated charcoal 1,5 g.l-1, KH 2A2 : Kristalon green 2 g.l-1 + Activated charcoal 2 g.l-1 , Vb2A0 : Vitabloom 2g.l-1 + Without activated charcoal, Vb2A1/2 : Vitabloom 2 g.l-1 + Activated charcoal ½ g.l-1, Vb2A1: Vitabloom 2 g.l-1 + Activated charcoal 1 g.l-1, Vb2A11/2: Vitabloom 2 g.l-1 + Activated charcoal 1,5 g.l-1, Vb2A2: Vitabloom 2 g.l-1 + Activated charcoal 2 g.l-1. The results obtained; (1)) The use of foliar fertilizers vitabloom 2 g.l-1 with the addition of activated charcoal 1,5 g.l-1 showed the best response by producing the highest plant height althought not substantially different with the addition of activated charcoal ½ g.l-1and 1 g.l-1 and the biggest wet crop weight. (2) Media vitabloom fertilizers and without activated charcoal shows a poor response. Keywords : Foliar fertilizers, activated charcoal, Phalaenopsis